Elucidation of Nutritional Quality, Antinutrients, and Protein Digestibility of Dehulled and Malted Flours Produced from Three Varieties of Bambara Groundnut (Vigna subterranean) - Mpho Edward Mashau; Thakhani Takalani; Oluwaseun Peter Bamidele; Shonisani Eugenia Ramashia (Foods)
Bambara groundnut (Vigna subterranean) is an important legume grain in sub-Saharan Africa, including South Africa. Nevertheless, the peculiarity of being hard to cook and mill and the availability of antinutritional factors often limit Bambara groundnut (BGN) use in food applications. This study investigated the impact of dehulling and malting on the nutritional composition, antinutritional factors, and protein digestibility of flours obtained from three BGN varieties (red, cream, and brown). Dehulling and malting significantly enhanced the moisture and protein content of BGN flours (dry basis), with values varying from 6.01% (control brown variety) to 8.71% (malted cream and brown varieties), and from 18.63% (control red variety) to 21.87% (dehulled brown), respectively. Dehulling increased the fat content from 5.82% (control red variety) to 7.84% (dehulled cream), whereas malting decreased the fat content. Nevertheless, malting significantly increased (p < 0.05) the fiber content from 4.78% (control cream) to 8.28% (malted brown variety), while dehulling decreased the fiber content. Both processing methods decreased the ash and carbohydrate contents of the BGN flours. Dehulling and malting significantly enhanced the amino acids of BGN flours, except for tryptophan and asparagine. Dehulling and malting notably increased the phosphorus, magnesium, potassium, and sulfur contents of the BGN flours, while calcium and zinc were reduced. Malting significantly enhanced the iron content of BGN flour, whereas dehulling reduced it. Both processing methods significantly enhanced palmitic, arachidic, and y-Linolenic acids. Nonetheless, processing methods significantly reduced phytic acid and oxalate, and dehulling achieved the most significant reductions. Dehulling and malting significantly enhanced the protein digestibility of the BGN flours from 69.38 (control red variety) to 83.29 g/100 g (dehulled cream variety). Overall, dehulling and malting enhanced the nutritional quality and decreased the antinutritional factors of BGN flours.